Clinicopathologic profile of intra-abdominal follicular dendritic cell sarcoma: A study of three cases with a literature review - Jianhong Yan; Qi Wu; Yuchang Hu; Ting Nai (Indian Journal of Pathology and Microbiology)
Follicular dendritic cell sarcoma (FDCS) is a rare tumor, which mainly originates from follicular dendritic cells (FDCs) in the lymph nodes. Sometimes FDCS can arise from outside the lymph nodes. FDCS is an extremely rare malignant tumor in intraperitoneal or retroperitoneal tissue. We gathered the detailed clinical data of three patients diagnosed with FDCS in the abdomen. The clinical observations and histopathologic and immunohistochemical features of FDCS were analyzed. The patients included two men and one woman aged 55 ~ 61 years old. The mesentery of the small intestine and colon was involved in case 1, spleen in case 2, and retroperitoneal tissues in case 3. Two patients presented with abdominal masses, and one presented with no obvious symptoms. Histology showed ovoid to spindle neoplastic cells arranged in fascicles and storiforms with inflammatory infiltrate as well as whorled patterns in some areas. Immunohistochemical staining was positive for CD21, CD23, CD35, and SSTR2. FDCS exhibits no characteristic clinical manifestations. Morphologically, FDCS can have overlapping features with many other entities, leading to misdiagnosis. The use of histopathology supplemented with FDC markers, such as CD21, CD23, and CD35, is useful for diagnosis and differential diagnosis.